A Systematic Review on Market Orientation and Marketing Performance in SMEs - Indarwati, Tias; R.A Sista Paramita; Ujang S. Mubarok; Nadia Asandimitra; Achmad Kautsar (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study examines the impact of market orientation on the marketing performance of small and medium enterprises (SMEs). Additionally, it identifies mediating and moderating factors that either strengthen or weaken this relationship. Design/Methode/Approach: A Systematic Literature Review (SLR) method was employed using a bibliometric approach to map research trends. The selection process adhered to the PRISMA framework, with an analysis of studies sourced from the Scopus database. Research Finding : The findings indicate that market orientation plays a crucial role in enhancing SME marketing performance. However, its effectiveness is influenced by product innovation, marketing capabilities, digital adoption, and external factors such as regulations and market competition. Theoretical contribution/Originality: This study enriches the literature on market orientation and marketing performance in SMEs through a systematic synthesis. The findings highlight the importance of integrating market orientation with innovation and digitalization to improve SME competitiveness. Practitioner/Policy implication: For SME practitioners, this study underscores the importance of market-oriented marketing strategies supported by innovation and digitalization. Moreover, policymakers should facilitate access to financing and digital marketing training for SMEs to enhance their market performance. Research limitation: This study is limited to a literature review and does not capture the dynamic challenges faced by SMEs directly.